2023
DOI: 10.1186/s40246-023-00456-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of genetic testing in the diagnostic workflow of pediatric patients with kidney diseases: the experience of a single institution

Abstract: Purpose Inherited kidney diseases are among the leading causes of kidney failure in children, resulting in increased mortality, high healthcare costs and need for organ transplantation. Next-generation sequencing technologies can help in the diagnosis of rare monogenic conditions, allowing for optimized medical management and therapeutic choices. Methods Clinical exome sequencing (CES) was performed on a cohort of 191 pediatric patients from a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Complete molecular mechanisms encompassing the structure and function of protein are difficult to identify from a single panel of genetic testing. Therefore, structural and functional protein studies may provide better evidence when the genetic mutation is not identified in standard testing [89][90][91]. Genetic testing would help plan or anticipate the natural course of illness, as in the present study CEP 290 mutation would have guided the clinicians and families for early renal replacement therapy or enrolling in renal transplant lists.…”
Section: Genetic Testingmentioning
confidence: 86%
“…Complete molecular mechanisms encompassing the structure and function of protein are difficult to identify from a single panel of genetic testing. Therefore, structural and functional protein studies may provide better evidence when the genetic mutation is not identified in standard testing [89][90][91]. Genetic testing would help plan or anticipate the natural course of illness, as in the present study CEP 290 mutation would have guided the clinicians and families for early renal replacement therapy or enrolling in renal transplant lists.…”
Section: Genetic Testingmentioning
confidence: 86%
“…Pediatric kidney diseases include a wide range of disease entities with varying clinical manifestations, courses of development, and treatment choices. Children with end-stage renal disease constitute a greater portion of the monogenic condition population, accounting for almost 30% of children with chronic kidney disease (CKD) [1]. Globally, pediatric CKD has a severe impact and is linked to high cardiovascular and allcause death rates, as well as significant morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly, genomics is being incorporated into the standard of care for children and their families with kidney disease, primarily as a diagnostic tool but also to guide therapy [7]. The use of next-generation sequencing techniques has greatly increased the diagnostic yield in patients with inherited kidney disorders, according to findings of numerous groundbreaking studies [1,3,4]. In the present review, we aim to collect all potential evidence from relevant studies that reported the role of genetic testing in pediatric renal disease diagnostic, prognostic, and social implications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations